Dream big dreams : photographs from Barack Obama's inspiring and historic presidency - Pete Souza (, New York, Little, Brown and Company, 2017)
Pete Souza served as Chief Official White House Photographer for President Obama's full two terms. He was with the President during more crucial moments than anyone else - and he photographed